Determining Pre-Service Business Education Teachers’ SelfReliance Levels In Pedagogical Content Knowledge In Kogi State, Nigeria - James Omatule Oborah; Dorcas Omanyo Oluwade; Margaret Ube Oborah (SOSEARCH : Social Science Educational Research, 2022)
With the new normal occasioned by advancement in technology and impact of COVID-19 pandemic, this study investigated business teachers’ self-reliance levels on technological pedagogical content knowledge (TPACK). This study investigated preservice business education teachers’ ratings of self-reliance level in pedagogical content knowledge. Through online survey on convenience sampling technique, data was generated from 105 respondents in Kogi state which was analyzed using descriptive and inferential statistics to answer the two research questions and a hypothesis raised for the study. The results showed that business teachers had low self-reliance ratings on the seven domains of the TPACK irrespective of the educational levels. Thus, it becomes imperative to revamp the business education teacher training programs through emergency attention in funding and capacity building.